2001
DOI: 10.1001/archinte.161.17.2099
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Care, Illness Severity, and Outcomes in the Management of Community-Acquired Pneumonia at Academic Hospitals

Abstract: Achieving process-of-care markers was not associated with improved outcomes, but was related to the severity of pneumonia as assessed on admission. Our results highlight the difficulty in demonstrating a link between process-of-care markers and outcomes in observational studies of CAP. Randomized studies are needed to objectively evaluate the impact of process-of-care markers on CAP outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 18 publications
3
54
0
3
Order By: Relevance
“…47 The American Thoracic Society has recommended this test since the 1990s as part of the initial evaluation of patients with CAP. 48 This recommendation was based on the belief that BC results facilitate more effective antimicrobial treatment because bacteremia refl ects more severe disease and a higher risk of mortality.…”
Section: An Official Journal Of the American Academy Of Pediatricsmentioning
confidence: 99%
“…47 The American Thoracic Society has recommended this test since the 1990s as part of the initial evaluation of patients with CAP. 48 This recommendation was based on the belief that BC results facilitate more effective antimicrobial treatment because bacteremia refl ects more severe disease and a higher risk of mortality.…”
Section: An Official Journal Of the American Academy Of Pediatricsmentioning
confidence: 99%
“…The evidence linking the pneumonia measures, for instance, to significant outcomes such as lower mortality or (rarely studied) better functional outcomes is extremely limited or nonexistent. 3,4 At the other end of the continuum are sweeping metrics such as risk-adjusted in-hospital mortality, which may be important and yet has 2 significant limitations. First, mortality rates in acute care are generally so low that this is not a useful outcome of interest for most clinical conditions.…”
mentioning
confidence: 99%
“…Mean LOS for the general North American patient population hospitalized with CAP is 5.8-9.8 days. 20,21 Another study examined LOS in CAP and found that in a somewhat similar population (veterans with multiple comorbid illnesses) the average LOS ranged from 4.6 to 9.7 days. 22 The prolonged LOS is noteworthy as studies have shown that LOS can at least be partially reduced with little impact on outcomes.…”
Section: Discussionmentioning
confidence: 99%